A new method for the treatment of myocardial ischemia-reperfusion injury based on γδT cell-mediated immune response - Luo, Wei; Bian, Xiaohong; Liu, Xiaona; Zhang, Wenchao; Xie, Qing; Feng, Limin (Frontiers in Cardiovascular Medicine, 2023)
Acute myocardial ischemia is a disease with high morbidity and mortality, and re-perfusion is currently the best intervention. However, re-perfusion may lead to further myocardial injury and increase the area of myocardial infarction [1,2] .The mechanism of myocardial ischemia-re-perfusion injury is complex, but with more in-depth study, it has been proved that the immune system plays an important role in the process of MIRI [3,4] .Among them, the γδT cell population has received increasing attention as the main early source of IL-17A in many immune response models.Because γδT cells have the characteristics of linking innate immunity and adaptive immunity,they can rapidly produce IL-17A and produce subsequent immune killing of cardiomyocytes. It can be seen that γδT cells play an important role in MIRI.Therefore, here we review the research progress of immune response in myocardial ischemia-re-perfusion injury, the key characteristics of γδT cells and the role of rapidly produced IL-17 in myocardial ischemia-re-perfusion injury, and propose relevant treatment strategies and prospects for myocardial repair, in order to provide new ideas and methods for clinical treatment of myocardial ischemia-re-perfusion injury.